2017
DOI: 10.25269/jsel.v7i02.215
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH KONDISI KULTUR PADA AKTIVITAS SELULASE ISOLAT Pycnoporus sp. DAN Phlebiopsis sp. (EFFECTS OF CULTURE CONDITIONS ON CELLULASE ACTIVITIES PRODUCED BY Pycnoporus sp. AND Phlebiopsis sp.)

Abstract: ABSTRAKPenelitian pengaruh media kultivasi, pH dan suhu inkubasi terhadap produksi enzim selulase-kompleks dari Pycnoporus sp. FORDACC-03452 dan Phlebiopsis sp. FORDACC-02482 yang ditumbuhkan di media dedak padi dan tongkol jagung dengan metode kultur padat pada variasi pH 4-7 dan suhu 30°C-45°C, telah dilakukan. Hasil memperlihatkan bahwa media dedak padi cenderung menginduksi produksi endo-β-1,4-glukanase dan selobiohidrolase, sedangkan media tongkol jagung menginduksi produksi β-glukosidase. Namun, campuran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…and Phlebiopsis sp. are some of the white rot fungi that have been studied for their cellulase activity, which demonstrated that the Pycnoporus isolate produces cellulase with higher activity than the Phlebiopsis isolate (Agustini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Phlebiopsis sp. are some of the white rot fungi that have been studied for their cellulase activity, which demonstrated that the Pycnoporus isolate produces cellulase with higher activity than the Phlebiopsis isolate (Agustini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pycnoporus sp. and Phlebiopsis sp., whose cellulolytic activities have been characterized (Agustini et al, 2017), can be tested for this purpose. Moreover, a study reported that the presence of carbonaceous products stimulated the proliferation of soilresident fungi and enhanced the enzymatic activities (Taskin, Teresa, Altomare, & Loffredo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The absorbance value of the supernatant was measured with a spectrophotometer at a wavelength of 500 nm. Cellulase activity was calculated based on the reducing sugar value obtained using the formula in equation (1).…”
Section: Cellulase Activity Assaymentioning
confidence: 99%
“…Cellulase is an enzyme complex capable of breaking down cellulose into glucose monomers. This complex comprises endocellulase, exocellulase, and β-glucosidase, which, in microorganisms, work synergistically to break down cellulose polymer chains [1,2]. Cellulase has been widely utilized in various fields, including textile, animal feed, agriculture, pharmaceutical, detergent, bioconversion, paper, and pulp industries [3,4].…”
Section: Introductionmentioning
confidence: 99%